STRATEGI PENGEMBANGAN PEMASARAN PUPUK KOMPOS ORGANIK PADA YAYASAN PEMILAHAN SAMPAH TEMESI, KABUPATEN GIANYAR - Dewa, Paksi Bali; Sudarma, I Made; Oka Suardi, I Dewa Putu (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2019)
The waste problem is not only related to the production and its transportation, but also concerning the sorting of organic and non-organic types. Temesi landfills in Gianyar Regency through the Yayasan Pemilahan Sampah Temesi (YPST) has a waste sorting activity to be used as a more economical product, namely compost fertilizer "Temesi Organik". The organic fertilizers usage in Bali Province in the last five years (2013-2017) has always been with an average of 28,897 tons. This potential will be a marketing opportunity for organic fertilizer producers in Bali Province. But YPST facing a problem lack of good planning in terms of product marketing. The purpose of this study was to analyze internal and external factors, formulate alternative strategies, and determine the priority strategies in developing marketing of compost fertilizer "Temesi Organik". Data analysis methods used are SWOT and AHP analysis. The results of the study based on the SWOT analysis obtained six alternative strategies namely improving product quality to maintain customer loyalty and the synergy of government policies, maintaining product continuity to reach the organic fertilizers market potential, maintaining the legality of organic certification, expanding market networks by utilizing social media and word of mouth marketing methods, complementing facilities and production infrastructure in composting, and improving the quality of human resources to produce products with a strong bargaining position. Based on AHP analysis obtained the main priority of six alternative strategies is to expand the market network by utilizing social media and the word of mouth marketing method. Keywords: Marketing Strategy, Organic Compost Fertilizer, Yayasan Pemilahan Sampah Temesi